Studying Key Factors and Models of Instruction of Vocal Music Interpretation for 9-11 Years Old Learners - Sirikul, Jirapinya; Thuntawech, Saya (An Online Journal of Education, 2023)
This qualitative research aimed: to study key factors and models of instruction of vocal music interpretation for learners aged 9-11 years old. Data were gathered from documents and in-depth interviews with seven key informants, obtained by purposive sampling, and analyzed using content analysis method. The results were divided into two sections. Section 1, the factors of instruction of vocal music interpretation consisted of 3 parts: 1) The skills related to and affecting the learning of vocal music interpretation, i.e., music skills, vocal techniques skills, movement skills, language and communication skills, and concentration control skills 2) The condition of song selection for teaching interpretation of singing songs, according to the learner development and elements of music that promotes learning of vocal music interpretation and 3) The other factors involved in song interpretation learning. Section 2, the models of instruction of vocal music interpretation for learners aged 9-11 years old, divided into three main steps, 1) understanding the form of the song by listening and reading 2) connecting to the song by correlating the learner’s experience or imagination 3) communicating meaning through singing acting, and movement.